(untitled) - Gilfillan, S. C. (Cambridge, 1935)
That invention is an important subject for modern mankind to understand and perhaps later improve, all will agree. That invention is partly caused, hampered, promoted, steered by social factors and institutions (such as wealth, or the patent system) and not simply by developments in the physical sciences and industrial practice, will also be allowed. (How great is the social causation we shall discuss.) Likewise that inventions have wide social, and not simply industrial effects, has been common knowledge for nigh a century. There would seem then every call for a treatise on the Sociology of Invention. Yet not one book with this definitive field has been published in any language....
Keywords: Inventions,Ships,Sáng chế,Tàu thuyền